Parenchymal pressure injury Ca2+ entry mechanism in pancreatitis. (June 2020) - Sutton, Robert
Abstract: Pancreatic trauma and high parenchymal pressure have been found to open Piezo1 plasma membrane Ca 2+ channels to such an extent that transient receptor potential vanilloid type 4 channels also open to further Ca 2+ entry, overloading the cell with Ca 2+ to induce acute pancreatitis (Swain et al, J Clin Invest, 2020). Elucidation of this mechanism is an important step in understanding pancreatitis and opens up new possibilities for prevention and treatment.